Syphilis : Medicine, Metaphor, and Religious Conflict in Early Modern France - Losse, Deborah N., 1944- (Book collections on Project MUSE., 2014)
"In Syphilis: Medicine, Metaphor, and Religious Conflict in Early Modern France, Deborah Losse examines how images of syphilis became central to Renaissance writing and reflected more than just the rapid spread of this new and poorly understood disease. Losse argues that early modern writers also connected syphilis with the wars of religion in sixteenth-century France. These writers, from reform-minded humanists to Protestant poets and Catholic polemicists, entered the debate from all sides by appropriating the disease as a metaphor for weakening French social institutions. Catholics and Protestants alike leveled the charge of paillardise (lechery) at one another. Losse demonstrates how they adopted the language of disease to attack each other's politics, connecting diseased bodies with diseased doctrine. Losse provides close readings of a range of genres, moving between polemical poetry, satirical narratives, dialogical colloquies, travel literature, and the personal essay. With chapters featuring Erasmus, Rabelais, Montaigne, Lery, and Agrippa d'Aubigne, this study compares literary descriptions of syphilis with medical descriptions. In the first full-length study of Renaissance writers' engagement with syphilis, Deborah Losse charts a history from the most vehement rhetoric of the pox to a tenuous resolution of France's conflicts, when both sides called for a return to order"--Provided by publisher.